Financial integration of stock markets in the Gulf Cooperation Council countries - Alsuhaibani, Saleh I., author; Fan, Liang-Shing, advisor; Bernasek, Alexandra, committee member; Olienyk, John, committee member; Kling, Robert W., committee member (Colorado State University. Libraries, 2004)
The purpose of this study was to establish the level of integration that exists among the GCC stock markets and between GCC stock markets and major international markets. The research defines market integration in terms of co-movement of stock prices. Markets are considered to be integrated if national stock prices share a common long-run relationship. Correlation, cointegration analysis, and Granger causality tests were applied in the investigation of the stock markets' integration. The five GCC stock markets included in the analyses represent five GCC states—Bahrain, Kuwait, Oman, Qatar, and Saudi Arabia. The measures of major international stock markets were applied to stock markets in the United States (S&P 500), the United Kingdom (FTSE 100), and Japan (Nikkei 225). Additionally, the Morgan Stanley Capital International Index (MSCI) reflected all major stock markets on a global basis. Weekly country equity market indices were collected for the period from August 1998 to August 2003. Evidence of cointegration was found for some pairs of the GCC stock markets during the five-year period. Multilateral cointegration of the five markets was established minimally among these markets as a group. Contemporaneous correlations among the GCC markets are less than perfect. However, the estimates suggest considerable effects of variations in one market on another. The study suggests that the GCC stock markets, except the BSE, are not cointegrated with the developed markets, which indicates that there is considerable evidence of the diversification benefits of investing in the emerging markets of the Gulf region. That is consistent with results of the correlation analysis, which found negative correlations among GCC and developed stock markets. The UK market is found to be the most influential market, while the US market is the least influential market affecting stock markets in the GCC countries.
Keywords: finance; integration; studies; investigations